Modern criminal evidence - Gourlay, Matthew (Emond, 2022)
"This book is our first major treatise in criminal law, a substantive modern interpretation of the law of evidence in Canada. It differentiates itself from the major treatises offered by other publishers by emphasizing practical guidance, advocacy tactics, a balance between Crown and defence perspectives, national context, and a more focused and succinct treatment than the more academic treatises. As an evidence treatise, the book is one of general application, covering issues relevant to all types of Canadian criminal offences."– Provided by publisher.